Laser ablation-ICP-TOFMS imaging of germ cell tumors of patients undergoing platinum-based chemotherapy. Issue 8 (11th June 2020) - Theiner, Sarah; Schweikert, Andreas; Haberler, Christine; Peyrl, Andreas; Koellensperger, Gunda
Abstract : A low dispersion laser ablation setup in combination with inductively coupled plasma-time-of-flight mass spectrometry (LA-ICP-TOFMS) was applied to clinical samples of patients undergoing platinum-based chemotherapy. Abstract : A low dispersion laser ablation setup in combination with inductively coupled plasma-time-of-flight mass spectrometry (LA-ICP-TOFMS) was applied to clinical samples of patients undergoing platinum-based chemotherapy. The platinum accumulation together with the distribution of elements with biological key functions (Mg, P, S, Ca, Fe, Cu and Zn) was studied in central nervous system germ cell tumor (CNS GCT) tissue, which is an aggressive tumor type located in the brain. Heterogeneous elemental distribution patterns were obtained with a pixel size of 10 μm and were correlated to histological analysis of serial sections using hematoxylin eosin staining. Highest platinum accumulation correlated with areas of necrosis, which exhibited high levels of magnesium, sulphur and calcium. Small traces of gadolinium were found in the tumor sections, which is a result of prior magnetic resonance imaging. Iron accumulated in regions, which were dense in blood vessels, whereas areas with fibrosis scar showed the lowest levels of all detected elements. This LA-ICP-TOFMS study demonstrates that the chemotherapeutic drug cisplatin accumulated in the germ cell tumor located in the brain, which is also reflected by the therapy response of the patients.